Waste management: a qualitative study exploring the perception of flood waste management among the community of Pasir Mas - Mohd Saat, Nur Zakiah; Abdul Wahab, Muhammad Ikram; Mohd Saat, Nur Ashikin; I., Zawaha; H., Siti Aishah; Abd Warif, Nor Malia; M., Siti Norasmarina; S. M. S., Muhammad Mustaqim (Faculty of Design & Architecture, Universiti Putra Malaysia, 2015)
The purpose of this paper is to examine the 2014 post-flood waste management in affected area. For this purpose, Pasir Mas in Kelantan was chosen as the sample area and interviews were conducted with the residents. The interviews aim to gather information about post-flood waste produced, sources of the waste, actions taken by the residents and related authorities bodies to clear the waste, impact of the waste on their living surroundings and health, and assistance needed to manage the waste. A total of 39 respondents consisted of 20 men and 19 women were selected at random for focus group discussion. These respondents represent persons of age 25 years old and above, local and whose living quarters have been affected by the flood. The large volume of mud left by the flood has been identified by the participants as the main source of the post-flood waste. In addition, good cooperation between government agencies and the residents is important to speed up the waste clearing works. However, residents are in much needed support, awareness and education about the impact of long due waste clearing on their health and living environment.